RGEC-Based Comparative Study of Health Levels in Indonesia's Sharia Banks (2019-2023) - Subardi, Hani Meilita Purnama (Future Science, 2024)
This research aims to analyze the comparative health ratings of Islamic banking using the RGEC method based on the regulations established by Otoritas Jasa Keuangan (OJK) No. 4/PJOK.03/2016 concerning the Assessment of Commercial Bank Health Levels. This study employs descriptive research with a quantitative approach. The data sources used include the annual reports and GCG reports of Islamic Banks from 2019 to 2023.The results of this study indicate that Islamic banks in Indonesia have achieved varied health ratings. Bank Aceh Syariah, Bank NTB Syariah, and BCA Syariah received the